E-Module of Macapat Song Art Course to Improve Effectiveness of Students' Independent Activities - Latif Nur Hasan; Marsudi Marsudi; Respati Retno Utami; Meirina Lani Anggapuspa; Adinda Alfiranda Zahroh (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
This study aims to analyze the effectiveness of e-modules designed with a step-by-step exercise model in supporting student activities in learning Tembang Macapat. The research was conducted using classroom action research involving five main learning activities, including notation practice and vocal exercises. Observations were made over two learning days. Results showed that students initially focused heavily on complex tasks, while simpler tasks were completed more gradually. On the second day, student performance became more balanced and efficient, indicating adaptation to the structured e-module design. Activity 4 showed increased engagement, reflecting deeper cognitive involvement. The findings suggest that structured e-modules can improve learning efficiency and student independence in traditional music education. This study contributes to the integration of local cultural content into digital learning tools and offers a practical model for designing adaptive and culturally responsive learning resources in arts education.